Поддержка решений функциональных пользователей в интеллектуальных системах управления предприятием - Тимашова, Л. А.; Тур, Л. П.; Лещенко, В. А.; Яненко, Л. А. (Видавництво Львівської політехніки, 2011)
This report had considered an approach for building decision support systems based on knowledge space,which is used for the conceptualization of the ontological approach.
Keywords: интеллектуальные системы управления; поддержка решений; пространство знаний; онтология